Evidence for structural deformation of the DNA helix by a psoralen diadduct but not by a monoadduct. - Shi, Y B (1988)
We have investigated the structural change in a double-stranded DNA helix caused by covalent addition of a psoralen. A synthetic double-stranded DNA was constructed to contain either a psoralen furan-side monoadduct or an interstrand diadduct at a specific site. When the unmodified and psoralen modified DNAs were examined by electron microscopy in the presence of distamycin, which stiffens the DNA helix, the DNA containing the psoralen interstrand diadduct appeared bent (or kinked), whereas the furan-side monoadducted DNA appeared similar to the unmodified DNA. RecA protein from E. coli has been shown to preferentially bind UV (ultra violet) irradiated DNA presumably due to alterations in the normal DNA helical structure. Using a nitrocellulose filter binding assay, we have found that the psoralen interstrand diadduct enhances the binding of recA protein to the double-stranded DNA, whereas a furan-side monoadduct has little effect. Thus both the recA protein binding and the electron microscopic data suggest that a psoralen diadduct causes deformation of a DNA helix, most likely by kinking the helix, and that a monoadduct has little effect on the DNA helix structure.